Principal–principal agency conflict and information quality in China: The governance role of audit quality and analyst following. Issue 1 (11th March 2019) - Safdar, Raheel; Chaudhry, Naveed Iqbal; Mirza, Sultan Sikandar; Yu, Yan
Abstract : Purpose: This study aims to examine the role of principal–principal (P–P) agency conflict in shaping the information environment of firms in China. Moreover, it investigates whether audit quality and analyst following play any role in moderating the effects of P–P agency conflict. Design/methodology/approach: The authors used principal component analysis to synthesize a measure of P–P agency conflict and used accruals quality as measure of information quality. They used two-step Arellano Bond system GMM estimators to cope with potential endogeniety in the model. Moreover, they also performed subsample analyses based on state ownership to ensure the robustness of findings. Findings: The results of this paper provide evidence that high P–P agency conflict is associated with poor information quality in China. But this is not true for subsample of state-owned enterprises. Moreover, better audit quality and high analyst following mitigate the negative effects of high P–P agency conflict on information quality but only in subsample of non-state-owned enterprises. Originality value: The findings of this paper are important, as they contribute in literature on forces shaping the information environment of firms. Moreover, it presents audit quality and analyst following as external governance mechanisms to alleviate the negative consequences of the P–P agency conflict vastly embedded in the ownership structure of firms in China.